Sudden Stops, Output Drops, and Credit Collapses - Dagher, Jihad (IMF Working Papers; Working Paper ;, 2010)
This paper proposes a tractable Sudden Stop model to explain the main patterns in firm level data in a sample of Southeast Asian firms during the Asian crisis. The model, which features trend shocks and financial frictions, is able to generate the main patterns observed in the sample during and following the Asian crisis, including the ensuing credit-less recovery, which are also patterns broadly shared by most Sudden Stop episodes as documented in Calvo and others (2006). The model also proposes a novel explanation as to why small firms experience steeper declines than their larger peers as documented in this paper. This size effect is generated under the assumption that small firms are growth firms, to which there is support in the data. Trend shocks when combined with financial frictions in this model also generate strong leverage effects in line with what is observed in the sample, and with other observations from the literature.